Diagnostic value of plasma HSP90α levels for detection of hepatocellular carcinoma - Wei, Wene (BMC Cancer, 2020)
BACKGROUND: Hepatocellular carcinoma (HCC) is a major health problem worldwide. However, the popular tumor marker, AFP, lacks sensitivity although its specificity is high. Tissue biopsy is an invasive operation and may increase the risk of needle-track metastases. Heat shock protein 90 (HSP90) is a potential biomarker for tumor diagnosis and prognosis. This study aims to determine whether levels of plasma HSP90α in HCC patients can be used as a cost-effective and simple test for the initial diagnosis of the disease. METHODS: Plasma samples were collected from 659 HCC patients, 114 secondary hepatic carcinoma (SHC) patients, 28 hepatic hemangioma patients and 230 healthy donors. The levels of HSP90α were measured by ELISA. RESULTS: The levels of plasma HSP90α in HCC patients were significantly higher than in healthy donors and in patients with hepatic hemangioma or SHC (144.08 ± 4.98, 46.81 ± 1.11, 61.56 ± 8.20 and 111.96 ± 10.08 ng/mL, respectively; p < 0.05 in all cases). The levels were associated with age (p = 0.001), BCLC stage (p < 0.001), levels of AFP (p < 0.001), tumor size (p < 0.001), tumor number (p < 0.001), PVTT (p < 0.001), EHM (p < 0.001) and Child-Pugh stage in the HCC cohort. In addition, the levels of plasma HSP90α showed an upward trend along with the progression of the BCLC stage. ROC curve analysis showed that compared to AFP (AUC 0.922, 95%CI 0.902–0.938) or HSP90α (AUC 0.836, 95%CI 0.810–0.860), the combination of HSP90α and AFP (AUC0.943, 95%CI 0.925–0.957) significantly improved the diagnostic efficiency for HCC patients. CONCLUSION: The results suggest that plasma Hsp90 α levels can be used as an initial diagnosis for patients with HCC in both rural and cosmopolitan settings.